Download presentation
Presentation is loading. Please wait.
Published byJason Wilcox Modified over 9 years ago
1
MONOMIALS NUMERIC VALUES OPERATIONS POLYNOMIALS NUMERIC VALUES (GRAPHING) OPERATIONS IDENTITIES
2
A monomial with variable x is the product of a real number by a non-negative integer ax exponent co-efficientvariable The degree of a monomial in one variable corresponds to the exponent of the variable. The degree of a monomial with many variables is equal to the sum of the exponents. n
3
The numeric value of a monomial is obtained by replacing the variables by their corresponding given values. 3x - if x = 2, then 3 x (2) = 3 x 4 = 12. 22
4
ADDING/SUBTRACTING Two monomials using the same variables, each affected by the same exponents, are called “like terms”. The sum of difference of two monomials that are “like terms” can be reduced to a single monomial. Examples:3x + 5x = 8x 5x y - 3x y = 2x y 222 232323
5
To MULTIPLY/DIVIDE by a constant, multiply/divide the constant by the co-efficient Ex. 5 x (3x ) = (5 x 3)x = 15x 12x ÷ 3 = (12 ÷ 3)x = 4x To MULTIPLY/DIVIDE by another monomial use the following procedure (Law of exponents) Ex. 3x x 2x = 6x or -3x y x 5xy = -15x y 12x ÷ 6x = 2x 222 222 2352334 532
6
A polynomial in x is an algebraic expression formed by a monomial or the sum of monomials P(x) = 3x - 2x + 5 polynomial with a single variable P(x,y) = 2x y – 3xy + xy – 2x + 1 polynomial with two variables x and y Binomial:3x + 5x Trinomial: -2x + 3x – 1 Degree of a polynomial corresponds to the highest degree of any of its monomials once reduced 2 22 2 2
7
The numeric value of a polynomial is obtained by replacing the variables by their corresponding given values. Example:a stone is thrown from the top of a 25m cliff, represented by H(t)=-5t + 20t + 25. t= 3 sec: H(3)= -5(3 ) + 20(3) + 25 = - 45 + 60 + 25 = 40 “zero” of a polynomial is any value of the variable which makes the polynomial equal to zero H(5) = 0 2 2
8
H(t). (3,40) H(t) = - 5t +20t + 25 30. (0,25) 20 10. (5,0) 0t(s) 2
9
ADD/SUBTRACT: A(x) = 3x - 2x +5 and B(x) = 5x + 3x – 4 A(x) + B(x) = 8x + x + 1 A(x) – B(x) = -2x - 5x + 9 MULTIPLY: 3x (2x + 5x) = 6x + 15x (2x + 3)(5x – 2) = 2x(5x – 2) + 3(5x – 2) = 10x - 4x + 15x – 6 = 10x + 11x = 6 22 2 2 2353 2 2
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.